Предмет: Алгебра,
автор: duzez
Помогите упростить пример пж!!!
(m/n+n/m+2)(2+m-n/m+n)
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(m/n +n/m +2)(2+m -n/m +n)=(2m/n +m²/n +m +2n/m +n -n²/m² +n²/m +4+2m -2n/m +2n=(2m+m²)/n +3m+3n -(n²m-n²)/m² +4=(m²(2m+m²)+m²n(3m+3n+4)-n(n²m-n²))/(m²n)=(2m³+m⁴+3m³n+3m²n²+4m²n-n³m+n³)/(m²n)=(m⁴+2m³+3m³n+3m²n²+4m²n-mn³+n³)/(m²n)
Похожие вопросы
Предмет: Математика,
автор: uzkenovaakzan00
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: popwolfwtfolgarauwu2
Предмет: Математика,
автор: манзура8
Предмет: Математика,
автор: Arkas0523